Fermented Black Rice Extract (Oryza sativa) Induces Morphological Changes in Pathogenic Microorganisms - Wijayanti, Ernanin Dyah; Syafah, Lailiiyatus; Rahayu, Lina Oktavia; Wulandari, Dita; Ibrahim, Zalikha (Biosaintifika: Journal of Biology & Biology Education, 2025)
Black rice (Oryza sativa L.) contains nutrients and bioactive compounds with potential application in health, including antimicrobial properties. To date, the application of fermentation to black rice to enhance its bioactivity, particularly as an antimicrobial, remains unclear. This study aims to evaluate the antimicrobial activity of solid fermented black rice against Gram-positive bacteria, Gram-negative bacteria, and fungi. Black rice was fermented using Saccharomyces cerevisiae under solid-state conditions. Extraction was carried out by maceration using 96% ethanol. Antimicrobial activity was assessed using the well diffusion test method, agar dilution, and scanning electron microscope (SEM). Fermented black rice extract showed antimicrobial activity against all tested microbes. The minimum inhibitory value obtained was 20% against all microbes, but the minimum bactericidal/fungicidal concentration (MBC/MFC) could not be determined. The SEM analysis showed morphological changes in microbes exposed to fermented black rice extract, including cell shrinkage, elongation, and lysis in Bacillus cereus, fragmentation and irregular cell shape in Escherichia coli, cell size reduction in Staphylococcus aureus, and bleb formation in Candida albicans. These changes indicate the mechanism of microbial growth inhibition. We found that fermented black rice (EFBR) extracts produce different effects from unfermented black rice extracts (EUBR), which tend to induce biofilm formation. We propose that EFBR functions as an antimicrobial by rupturing cell walls, preventing cell division and DNA synthesis. This research provides new insights into natural antimicrobial mechanisms at the cellular level and offers a potential alternative for addressing antimicrobial resistance. Solid fermented black rice may serve as a valuable source of antimicrobial compounds for developing health products or natural preservatives.